Pratt family papers - Pratt, John, active 1802.; Pratt, Maria
School arithmetic copy book (1802) of John Pratt, and copy book for grammar and other subjects (1808) of Maria Pratt, of Port Royal, Va.
Collection material in English.
Keywords: Pratt family; Education -- Virginia -- Port Royal